The Potential Of Bacterial Endophyte Of Plants Paitan Titonia Deversifolia As Biofertilizer And Biopesticide: Potensi Bakteri Endofit Dari Tanaman Paitan Titonia Deversifolia Sebagai Biofertilizer dan Biopestisida - Desta andriani; M FIRDAUS OKTAFIYANTO (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2019)
The development of pathogen control is currently not only targeted at suppressing pathogens but also considered safe for the ecosystem by utilizing endophytic bacteria. Endophytic bacteria can live in plant tissues without causing symptoms of disease and have a positive influence on plant growth. This study aims to obtain potential endophytic bacteria from T. diversifolia. Of the 23 endophytic bacteria isolated and previously characterized there were 13 endophytic bacteria that had the potential to increase rice growth, namely isolates, Ta42t, Ta46t, Ta31n, Tb31t, Tb35t, Tb41t, Ta34n, Tb34n, Ta36n, Tb32t, Tb43n, Ta43n, Tb32n, Tb45n. Of the 23 isolates 3, endophytic bacterial isolates that can suppress pathogens are Tb45n, Tb42n and Ta43n isolates. There are 2 isolates that can be used as triggers for growth as well as can be used to suppress pathogen growth.